Analisis Eksegetis Makna Transfigurasi Yesus Menurut Injil Markus 9:2-8 Dan Implikasinya Bagi Orang Percaya - Suerandi, Dedi; Sanda, Hendrik Yufengkri (STT Pelita Dunia, 2025)
The transfiguration of Jesus in Mark 9:2-8 is a crucial moment in the Gospels that affirms Jesus' divine identity as the glorified Son of God and the redeemer of mankind. The importance of this study is motivated by the frequent historical-theological misunderstandings regarding the transfiguration, where some parties overemphasize His human nature, while others focus too much on His divine nature, resulting in an unbalanced teaching. The main objective of this study is to analyze the text of Mark 9:2-8 exegetically to uncover the deep theological meaning behind the event and its relevant implications for the lives of believers today. This study uses a qualitative method with an exegetical analysis approach. The study shows that the transfiguration was a revelation of Christ's glory before His suffering on the cross, serving as a confirmation of the disciples' faith. The presence of Moses and Elijah symbolized the fulfillment of the Law and the Prophets' Prophecies in Jesus. The voice of God the Father from the cloud affirmed Jesus' divine authority and demanded absolute obedience to Him. Implicatively, the transfiguration calls believers today to listen to and obey Christ, live a faith centered on His cross and resurrection, and hold fast to the hope of future glory. This event serves as a powerful invitation to strengthen faith and direct all aspects of life toward the glory of Christ amidst the challenges of our times.